Protective effect of xylosma congesta extract on renal injury in hyperuricemic rats - Jinjun He; Weiyi Tian; Yonghui Meng; An Yan; Xin Lai; Fei Wang; Bangwei Che (Heliyon)
Background: The purpose of this study was to investigate the protective effect of xylosma congesta extract on kidney injury in hyperuricemic rats. Methods: The rats were fed yeast extract and intraperitoneal injections of potassium oxonate for 3 weeks to establish the hyperuricemia model. And then the rats were treated with allopurinol and different doses of oak extract. The contents of uric acid in urine and serum, creatinine, and urea nitrogen in serum were detected by biochemical methods. TUNEL was used to detect cell apoptosis in renal tissue. The protein expression of TLR4 and NF- kappa B (NF-κB) p65 and the proportion of CD68 and CD206 positive cells in renal tissue were detected by pathological method. Results: The xylosma congesta group showed decreased renal tubular dilatation, decreased renal interstitial inflammatory cell infiltration, decreased serum creatinine content, and decreased apoptotic cell count as compared to the model group. And positive expression of TLR4 and NF-κB decreased with each dose. Additionally, the xylosma congesta groups showed a significant rise in CD206 and a considerable decrease in CD68. Conclusion: The extract from xylosma congesta has the ability to lower serum uric acid and creatinine levels while also providing protection against kidney damage caused by hyperuricemia.